2010
DOI: 10.2106/jbjs.j.00272
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the AAOS Leadership Fellows Program for Orthopaedic Surgeons

Abstract: The AAOS Leadership Fellows Program seems to have a positive impact on the leadership competency of its participants. Graduates of the program are more likely to assume leadership positions in national organizations and within their own institutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 10 publications
0
29
0
Order By: Relevance
“…Only 3 of the programmes assessed the leadership promotion of programme attendees. In one of the few controlled studies that were reviewed by Strauss et al ,13 Day et al 14 assessed the effectiveness of a leadership development programme for orthopaedic surgeons using eight parameters: knowledge of leadership theory, environmental scanning, financial management, communication skills, conflict management, diversity competence, tolerance for the demands of leadership and leadership positioning. Programme graduates (n=67) were compared with applicants who were not selected to participate (n=73).…”
Section: Introductionmentioning
confidence: 99%
“…Only 3 of the programmes assessed the leadership promotion of programme attendees. In one of the few controlled studies that were reviewed by Strauss et al ,13 Day et al 14 assessed the effectiveness of a leadership development programme for orthopaedic surgeons using eight parameters: knowledge of leadership theory, environmental scanning, financial management, communication skills, conflict management, diversity competence, tolerance for the demands of leadership and leadership positioning. Programme graduates (n=67) were compared with applicants who were not selected to participate (n=73).…”
Section: Introductionmentioning
confidence: 99%
“…Positive organizational outcomes are associated with multiple learning methods, including lectures, seminars, group work and learning in multidisciplinary teams . The annual American Academy of Orthopaedic Surgeons Leadership Fellows Program combines a mentorship programme with leadership training focusing on personal development, interpersonal skills, fundamentals of leadership, and leadership and managerial skills . Programme participants were more likely to assume leadership positions in national organizations and within their own institutions compared to non‐participants .…”
Section: Demographics Of Australian Orthopaedic Association (Aoa) Memmentioning
confidence: 99%
“…The annual American Academy of Orthopaedic Surgeons Leadership Fellows Program combines a mentorship programme with leadership training focusing on personal development, interpersonal skills, fundamentals of leadership, and leadership and managerial skills . Programme participants were more likely to assume leadership positions in national organizations and within their own institutions compared to non‐participants . However, as participants were selected for pre‐existing leadership qualities, the relative contribution of the programme to this outcome is uncertain.…”
Section: Demographics Of Australian Orthopaedic Association (Aoa) Memmentioning
confidence: 99%
“…Recent systematic reviews of leadership development programmes highlight that the impact is variable and in general modest; most studies report only basic learning outcomes (reaction to the programme or self-reported knowledge) and only a few refer to behavioural changes and system-level outcomes 12–14. For example, through objective measures, improved scores in leadership knowledge tests,15 possible improvement in decision-making skills16 and higher rates of advancement in administrative ranks17 have been identified. Occasional studies do report possible links to better patient care outcomes as measured objectively either in simulation settings18 or real-work settings, the latter only after long-duration leadership development programmes 19 20.…”
Section: Introductionmentioning
confidence: 99%